The Impact of the COVID-19 Pandemic on Relations in B2C Markets from the Point of View of Selected Buyer Characteristics - Adam SAGAN; Jarosław PLICHTA; Grazyna PLICHTA (Communications of International Proceedings, 2021)
The Covid-19 pandemic is a phenomenon affecting many socio-economic processes. It also affects the personal sphere of people, which often determines the change in behaviour, attitudes and the structure of values. Consequently, this has an impact on the exchange processes and relations among market players. The situation makes it possible to study and model these processes and react to similar shock phenomena in the future. The main research, carried out by the research team, was aimed at, e.g. creating and verifying descriptors describing the category of a pandemic as an exogenous shock and a multidimensional structural model allowing to study the relationship between an exogenous variable and endogenous variables, concerning both individual and relational factors. The article presents partial results of these studies which concern the assessment of the impact of the exogenous variable, which is the COVID-19 pandemic, on e-commerce relations, taking into account the mediating variables such as gender, age and education. It was hypothesised that the pandemic positively stimulates the development of e-commerce relations and that gender, age and education are the factors that differentiate the impact of COVID-19 on e-commerce relations. The article presents partial results regarding the relationship between consumers and e-commerce market players. For this purpose, the SEM path analysis methodology was applied.
Keywords: COVID-19 pandemic; path analysis; e-commerce; market segmentation